Kepala Sekolah Sebagai Pemimpin Visioner Di Era Society 5.0 - Hafizah, Nasywa; Auia Zayrin, Afifah; Hanifah, Haura; Hidayatullah, Rully; Harmonedi (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2024)
The role of school/madrasah principals in today’s educational landscape is increasingly complex and dynamic. As organizational leaders, principals are not only responsible for administrative management but must also ensure that all processes run efficiently and effectively. As educators, principals play a central role in enhancing educational quality by collaborating with teachers, students, and the community to create an excellent learning environment. On the other hand, their role as supervisors requires overseeing and mentoring the teaching quality and the professional development of teachers. However, the challenges faced by school/madrasah principals have intensified in the modern era, ranging from changes in educational policies, limited resources, to the challenges of digitalization in education. This article delves into the principal's duties and responsibilities across these three main roles, while also analyzing the contemporary issues they frequently encounter and offering strategic solutions to address these challenges.